Addressing Grammar in the Interaction Task-Based Learning Environment - Davis, Brent M. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
One of the major problems in language teaching is developing grammatical accuracy. This paper proposes that using error correction based on a functional grammar in a task-based learning approach may be a suitable solution. Towards this end an emic (using categories intrinsic to the language) functional grammar of the verb phrase is proposed and a description of how this fits into the focus on form component of task-based learning is provided.